2015
DOI: 10.18632/oncotarget.5830
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of linc-POU3F3 suppresses the proliferation, apoptosis, and migration resistance of colorectal cancer

Abstract: Long intergenic noncoding RNAs (lincRNAs) play important roles in regulating the biological functions and underlying molecular mechanisms of colorectal cancer (CRC). Here, we investigated the association of linc-POU3F3 and prognosis in CRC. We demonstrated that linc-POU3F3 was overexpressed in CRC tissues and positively correlated with tumor grade and N stage. Inhibition of linc-POU3F3 resulted in inhibition of cell proliferation and G1 cell cycle arrest, which was mediated by cyclin D1, CDK4, p18, Rb, and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 50 publications
(48 reference statements)
2
43
0
Order By: Relevance
“…In the present study, our data showed that ZEB1-AS1 was over-expressed in CRC tissues and positively correlated with tumor histology grade, N grade, and M grade. These results suggested that ZEB1-AS1 might be a potential diagnostic biomarker or therapeutic target in CRC [19][20][21]. To further understood the role of ZEB1-AS1 in CRC, we chose to detect changes in the biological behaviors in CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, our data showed that ZEB1-AS1 was over-expressed in CRC tissues and positively correlated with tumor histology grade, N grade, and M grade. These results suggested that ZEB1-AS1 might be a potential diagnostic biomarker or therapeutic target in CRC [19][20][21]. To further understood the role of ZEB1-AS1 in CRC, we chose to detect changes in the biological behaviors in CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a class of non-protein coding RNAs of more than 200 nucleotides, which are broadly distributed in the genome and can modulate gene expression [1922]. Recent accumulating evidence has demonstrated that lncRNA expression profiles are frequently changed in tumors compared to that of the adjacent non-tumorous tissues in numerous cancers [2327].…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, linc-POU3F3 was an oncogene that silencing linc-POU3F3 inhibited proliferation and migration, induced apoptosis in CRC. SMAD4, which is involved in TGF-β-induced autophagy, showed an increase because of linc-POU3F3 knockdown [52, 53]. In addition, autophagy related protein, BECLIN1, ATG5, ATG7, and LC3 II, were continually accumulated by linc-POU3F3 knockdown due to interdicted autophagy in CRC [53].…”
Section: The Role Of Lncrnas In Crcmentioning
confidence: 99%
“…SMAD4, which is involved in TGF-β-induced autophagy, showed an increase because of linc-POU3F3 knockdown [52, 53]. In addition, autophagy related protein, BECLIN1, ATG5, ATG7, and LC3 II, were continually accumulated by linc-POU3F3 knockdown due to interdicted autophagy in CRC [53]. This study declared that linc-POU3F3 exerts its functional potential by mediating CRC autophagy.…”
Section: The Role Of Lncrnas In Crcmentioning
confidence: 99%
See 1 more Smart Citation